2019
DOI: 10.1183/13993003.00169-2019
|View full text |Cite
|
Sign up to set email alerts
|

Connexin-43 is a promising target for pulmonary hypertension due to hypoxaemic lung disease

Abstract: The mechanisms underlying pulmonary hypertension (PH) are complex and multifactorial, and involve different cell types that are interconnected through gap junctional channels. Although connexin (Cx)-43 is the most abundant gap junction protein in the heart and lungs, and critically governs intercellular signalling communication, its contribution to PH remains unknown. The focus of the present study is thus to evaluate Cx43 as a potential new target in PH.Expressions of Cx37, Cx40 and Cx43 were studied in lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…Some early changes in HPH are difficult to detect with traditional research tools and expertise. Much effort has been afforded to finding new therapeutic targets and biomarkers for HPH (18)(19)(20)(21). Most studies, however, have focused only on mRNAs (18,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Some early changes in HPH are difficult to detect with traditional research tools and expertise. Much effort has been afforded to finding new therapeutic targets and biomarkers for HPH (18)(19)(20)(21). Most studies, however, have focused only on mRNAs (18,20,21).…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 28 , 29 Conversely, using a C57BL6 mouse model subjected to 14 days of hypoxia, we showed a decrease in Cx43 gene and protein expression in the pulmonary artery, 11 while another study found a 21-day hypoxic exposure to have no effect on CX43 gene expression in the CD1 mouse pulmonary artery. 9 Thus, Cx43 may be differentially regulated by hypoxia depending upon the strain/species as well as the duration of hypoxic exposure. While we may expect a correlation between changes in gene expression and changes in protein expression, this correlation can be as low as 40% in eukaryotes.…”
Section: Discussionmentioning
confidence: 53%
“…Interestingly, a previous study showed that Cx43 expression was increased in pulmonary arteries from patients with chronic hypoxic PH and that mice heterozygous for Cx43 were protected against hypoxic-induced pulmonary vascular remodelling. 9 Thus, the data presented in this manuscript build on the hypothesis that Cx43 may be a promising therapeutic target for the treatment of PH associated with chronic hypoxia.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Another study on pathological right ventricular cardiac hypertrophy in rats (caused by pulmonary resistance induced hypertension) revealed no increase in Cx43 expression. 40 However, redistributed lateral Cx43 was observed. The increased proportion of lateral Cx43 caused a significant decrease in longitudinal conduction velocity along the cardiomyocytes.…”
Section: Discussionmentioning
confidence: 94%